2015
DOI: 10.1519/jsc.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Successive Judo Matches on Fatigue and Muscle Damage Markers

Abstract: This study aimed to investigate the acute effects of simulated judo matches on fatigue and muscle damage markers. Twenty male judo athletes participated in this study. The athletes performed three 5-minute judo matches separated by 15 minutes of passive rest between each match. The following measurements were performed before and after each match: shoulder external/internal rotation isokinetic torque and countermovement jump (CMJ). Blood samples were taken before the first match and after the third match for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 22 publications
5
57
0
6
Order By: Relevance
“…Pinho Júnior et al 8 observed an inverse correlation between serum LDH and perceived muscle soreness (r ¼ À0.53) and upper limb power (r ¼ À0.32) in jiu-jitsu athletes who underwent CWI after simulated competition. Detanico et al 1 reported an increase in serum LDH levels and less lower limb power in judo athletes after 3 successive matches. According to Warren et al, 46 strenuous exercise caused structural disruption of sarcomeres, resulting in membrane damage and failures in the coupling process triggering muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinho Júnior et al 8 observed an inverse correlation between serum LDH and perceived muscle soreness (r ¼ À0.53) and upper limb power (r ¼ À0.32) in jiu-jitsu athletes who underwent CWI after simulated competition. Detanico et al 1 reported an increase in serum LDH levels and less lower limb power in judo athletes after 3 successive matches. According to Warren et al, 46 strenuous exercise caused structural disruption of sarcomeres, resulting in membrane damage and failures in the coupling process triggering muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, strenuous exercise promotes biochemical and cellular changes that result in deterioration of the muscle structure, decreasing muscle power. 2,3 In this context, many investigators have studied muscle damage arising from high-intensity exercise because it interferes with sport performance.…”
mentioning
confidence: 99%
“…Em esportes de combate, diversos estudos têm utilizado o desempenho no salto vertical com o intuito de verificar efeito de treinamento 21 , discriminar o nível competitivo [22][23] , sexo e categoria de peso 11,24 e como marcador de fadiga antes e após sequência de lutas [25][26][27][28] , como sintetizado na TABELA 4. Os valores de altura do salto obtido na presente investigação, considerando a média das categorias (45,4 ± 2,4 cm), é similar a alguns estudos 11,27 e superior aos demais [21][22]28 que analisaram esta variável para a mesma faixa etária e nível competitivo. Nenhum dos estudos analisados comparou o salto vertical entre categorias, considerando as variáveis antropométricas dos atletas.…”
Section: Discussionunclassified
“…Já foi evidenciado um aumento do dano muscular em atletas que não realizaram um polimento antes da competição, a exemplo do estudo de Marin et al 29 , com dez atletas de handebol avaliados antes de uma competição e após seis meses de treinamento específico. Detanico et al 30 , do mesmo modo, encontraram um aumento do dano muscular em 20 judocas, no entanto, estes atletas foram avaliados após sessões de lutas simuladas, possibilitando, assim, avaliar apenas a resposta fisiológica aguda.…”
Section: Discussionunclassified